52‐2: Ultrawide‐Color Gamut, Low‐Power Consumption White OLEDs for Large 8K OLED TV. Issue 1 (28th June 2022) - You, Juanjuan; Bo, Bin; Wu, Chang-Yen; Wang, Linlin; Shen, Yongqi; Song, Wenfeng; Yan, Guang; Sun, Li; Quan, Wei; Yu, Donghui; Wan, Xiang; Wang, Xinxin; et al.
Abstract : Next generation WOLED displays demand high color gamut and low power consumption, but it is a severe challenge for the WOLED display technology to meet the needs for high color gamut and low power consumption simultaneously. In this paper, with the optimization of WOLED spectrum which was well matched with CF, wide color gamut close to 99% at DCI‐P3 standard and lower power consumption of W/R/G/B as well as BDR power consumption is obtained.